ROLE OF VEGETABLE TRADERS WOMEN ON THE HOUSEHOLD INCOME - Sasmita Siregar; Khairunnisa Rangkuti; Yusuf Tri Darma (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
The aim of this study was to determine the effect of socio-economic factors (age, capital, experience, number of dependents and level of education) against income women vegetable vendors and to find out how much revenue the woman vegetable vendor to total household income. The study's hypotheses were tested using multiple linear regression analysis using SPSS. Results showed that simultaneously (synchronously) no influence of age, capital, experience, number of dependents and level of education on income women vegetable vendors. Partially capital and experience affect the earnings of women vegetable vendors, while age, number of dependents and level of education no effect. Income women vegetable vendors contribute fairly high on household income that is equal to 58.47 percent.Keywords: Women Vegetable Vendors, Household Income